Pengembangan Pariwisata Berkelanjutan Kawasan Candi Gedongsongo Kabupaten Semarang: Sustainable Tourism Development of Gedongsongo Temple Area, Semarang Regency - Pujianti, Fanny; Muh. Sholeh; M. Fikri Amrullah (Geo-Image Journal, 2025)
Tourism is one of the industrial sectors that is interrelated with all other sectors of life, such as economic, social, cultural, environmental, and political (Ardiansyah & Purnaweni, 2023). As in Central Java Province, which offers a variety of tourist attractions. The tourist attraction in Bandungan Subdistrict, namely the Gedongsongo Temple tourist attraction, is one of the leading cultural attractions in Bandungan Subdistrict. The number of tourists fluctuates, indicating high interest, although tourists' visits are usually short. Gedongsongo Temple has great tourism potential, and the sustainability of its management is the key to maximizing these benefits without damaging the environment or culture. In addition, based on observations and interviews that have been conducted, Gedongsongo Temple tourism has problems or obstacles including lack of promotion, lack of information related to Gedongsongo Temple, lack of quality and capacity of professional human resources in the tourism sector. So with these problems, sustainable tourism development is needed at Gedongsongo Temple. The purpose of this research is to describe the development of sustainable tourism in the Gedongsongo temple area in the socio-cultural, economic and environmental fields. This research method uses a quantitative descriptive approach with a quantitative research type. The population used is the tourist attraction managers, traders, and tourists, with the sample used being 100 visitors, one of the tourist attraction managers, and several traders. Data collection techniques through interviews, questionnaires, observation, and documentation. In addition, the data analysis technique used is descriptive percentage analysis. The results of this study are that Gedongsongo Temple has diverse cultural and artistic values with gamelan and dance performances, selametan activities, and temple cleaning activities. Visitors' perception of the value of culture and art is 70%. Vanaprastha accommodation that uses wooden buildings and eateries in the Gedongsongo Temple area sell traditional food. So that it still maintains the value of culture and art. In addition, the Gedongsongo Temple area is guarded by officers who operate every day. Visitors' perception of the tracking path is easy to pass by 70%. In addition to offering temples, it also offers horse rentals, photography services, hot springs, ayanaz, and supporting service facilities such as food stalls, souvenir shops, places of worship, toilets and landfills. Visitor perceptions regarding service facilities are 65% and 67% regarding electricity and communication networks and 59% regarding the facilities offered. Visitor perception regarding the use of local products is 60%. The price of souvenirs offered is also affordable, but based on interviews, Gedongsongo Temple does not yet have a distinctive local product as an icon of the tour itself. Visitors' perception of the scenery, water and air quality is 82%. The water comes from the Mount Ungaran spring, and the air is also cool because of the many trees. Visitors' perception of the cleanliness of the area is 63% and 69% regarding cleanliness and comfort at the tourist attraction.